2015
DOI: 10.3892/mmr.2015.3647
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin enhances proliferation and osteoblastic differentiation of human bone marrow stromal cells via a nitric oxide/cyclic guanosine monophosphate signaling pathway

Abstract: Puerarin, a major active isoflavone extracted from the Traditional Chinese Medicine Radix Puerariae, has been studied for its comprehensive biological effects. However, to date, its effect on bone formation and the underlying mechanism of action have not been well investigated. The present study investigated the effect of puerarin on cell proliferation and osteoblastic maturation in cultured human bone marrow stromal cells (hBMSC) in vitro. Puerarin (2.5-100 µM) increased hBMSC growth in a dose-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Through functional enrichment, we identified that NO can induce multiple molecular pathways such as protein kinase activity, estrogen receptor activity, BMP receptor binding, ligand-gated ion channel activity, or phosphatidylinositol 3-phosphate binding. Consistent with our results, many studies have demonstrated the relationship between NO and estrogen receptor signaling in several biological processes including osteogenic development [44][45][46]. Moreover, BMP signaling-induced NO production stimulated bone calcification in zebrafish [47].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 80%
“…Through functional enrichment, we identified that NO can induce multiple molecular pathways such as protein kinase activity, estrogen receptor activity, BMP receptor binding, ligand-gated ion channel activity, or phosphatidylinositol 3-phosphate binding. Consistent with our results, many studies have demonstrated the relationship between NO and estrogen receptor signaling in several biological processes including osteogenic development [44][45][46]. Moreover, BMP signaling-induced NO production stimulated bone calcification in zebrafish [47].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 80%
“…The increased synthesis of DNA may reflect more activities of cell proliferation. Previous studies have reported that puerarin enhanced the proliferation of human bone marrow stromal cells, and attenuated the proliferation of diabetes-induced vascular smooth muscle cells and bladder cancer cells [43][44][45], all of which is also beneficial to animals.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports have demonstrated that puerarin is able to promote osteoblast proliferation and differentiation ( 29 , 30 ). A study from Wong and Rabie ( 31 ) showed that puerarin treatment may prevent bone loss in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%